Faktor-Faktor Yang Mempengaruhi Produksi dan Analisis Pendapatan Usahatani Padi Sawah di Desa Namo Rambe - Ir. Cyprianus P.H. Saragi, MS (Jurnal Agriust, 2026)
This research aims to: (1) analyze what production factors influence lowland rice production in the research area, (2) determine the net income of lowland rice farming in the research area. The research area was determined purposively in Namo Rambe Village, Namo Rambe District, Deli Serdang Regency. The results of the research show that simultaneously seeds, urea fertilizer, phonska fertilizer, chlormite pesticide, gramoxone pesticide, and labor have a significant effect on the production of lowland rice farming. Partially, seeds, urea fertilizer, phonsa fertilizer, chlormite pesticide, gramoxone pesticide, and labor have a significant effect on lowland rice production. The net income of rice farming in the research area is IDR. 22,195,841.38/ha/MT with a selling price of Rp. 5,100/kg and total production of 6,896.77kg/ha/MT.